Stability analysis of oil yield in oil palm (Elaeis guineensis) progenies in different environments - Rafii, MY; Jalani, BS; Rajanaidu, N; Kushairi, A; Puteh, A; Latif, MA (Funpec-Editora, 2024)
We evaluated 38 dura x pisifera (DP) oil palm progenies in four locations in Malaysia for genotype by environment interaction and genotypic stability studies. The DP progenies derived from crosses between pisifera palms of AVROS, Serdang S27B, Serdang 29/36, and Lever Cameroon were chosen to be the males' parent and Deli dura palms designated as females' parent. All the locations differed in terms of soil physical and chemical properties, and the soil types ranged from coastal clay to inland soils. The genotype by environment interaction and stability of the individual genotypes were analyzed for oil yield trait using several stability techniques. A genotype by environment interaction was detected for oil yield and it had a larger variance component than genotypic variance (sigma(2)(gl)/sigma(2)(g) = 139.7%). Genotype by environment interaction of oil yield was largely explained by a non-linear relationship between genotypic and environmental values. Overall assessment of individual genotypic stability showed that seven genotypes were highly stable and had consistent performance over the environments for the oil yield trait [total individual genotype stability scored more than 10 and mean oil yielded above the average of the environment (genotype means are more than 34.37 kg.palm(-1).year(-1))]. These genotypes will be useful for oil palm breeding and tissue culture programs for developing high oil yielding planting materials with stable performance.